2021
DOI: 10.1111/cas.15206
|View full text |Cite
|
Sign up to set email alerts
|

Dvl2 facilitates the coordination of NF‐κB and Wnt signaling to promote colitis‐associated colorectal progression

Abstract: Colitis‐associated colorectal cancer (CAC) arises due to prolonged inflammation and has distinct molecular events compared with sporadic colorectal cancer (CRC). Although inflammatory NF‐κB signaling was activated by pro‐inflammatory cytokines (such as TNFα) in early stages of CAC, Wnt/β‐catenin signaling later appears to function as a key regulator of CAC progression. However, the exact mechanism responsible for the cross‐regulation between these 2 pathways remains unclear. Here, we found reciprocal inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…2) and have possible clinical implications for CRC prevention and therapy. This testing is of particular value given findings of the importance of various signaling pathways in CRC [24][25][26][27][28][29][30], including those that influence Wnt signaling [25,26,[28][29][30]. These other signaling pathways can be included in the categories of (a) receptor-mediated Wnt signaling and/or (b) those related to butyrate resistance [27], and the non-Wnt signaling pathways may exhibit cross-talk with Wnt activity, particularly Wnt activity that is mediated by CBP and p300.…”
Section: Discussionmentioning
confidence: 99%
“…2) and have possible clinical implications for CRC prevention and therapy. This testing is of particular value given findings of the importance of various signaling pathways in CRC [24][25][26][27][28][29][30], including those that influence Wnt signaling [25,26,[28][29][30]. These other signaling pathways can be included in the categories of (a) receptor-mediated Wnt signaling and/or (b) those related to butyrate resistance [27], and the non-Wnt signaling pathways may exhibit cross-talk with Wnt activity, particularly Wnt activity that is mediated by CBP and p300.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the essential role NF-κB and Wnt signaling play in CRC, previous studies have reported that elevated NF-κB levels enhance Wnt signaling, with de-differentiation of intestinal epithelial cells and the promotion of tumor initiation. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Mention crosstalk between stemness and immune cells, WNT signaling pathway, must not be overlooked. Tumor-derived WNT would induce a significant release of pro-inflammatory factors, like MPC-1 or IL-6, and attract numbers of immune cells to tumor immune niches helping cancer cells to escape from the immunologic killing, the function of nuclear factor-kB (NF-kB) signal pathway also contained [65][66][67]. Practically speaking, a conserved NF-kB binding site has been found on WNT5A, indicating that the activation of the WNT/b-catenin pathway could stimulate the vital position of NF-kB in both regulations of immune and inflammation [68,69 ].…”
Section: Targeting Crosstalk Between Lung Cancer Stem Cells and Tumor...mentioning
confidence: 99%